Letter to the editor. Concerning the article entitled ''Guillain Barre syndrome associated with COVID-19 infection: A case report". (September 2020) - Karimi, Narges; Sedaghat, Zahra
Highlights: A novel coronavirus (COVID-19) was detected in Wuhan City, Hubei Province of China. The most symptoms of disease have reported fever, cough, dyspnea, myalgia, headache, and diarrhea. We followed up GBS symptoms in one infected patient with COVID-19. The limbs weakness of patient completely improved after treatment with IVIG.